Modelling the potential distribution of the invasive tomato red spider mite, Tetranychus evansi (Acari: Tetranychidae) - Migeon, A.; Ferragut, F.; Escudero Colomar, L.A.; Fiaboe, K.K.M.; Knapp, M.; Moraes, G.J. de; Ueckermann, E.A.; Navajas, M. (Springer, 2009)
Predicting the potential geographical distribution of a species is particularlyimportant for pests with strong invasive abilities.Tetranychus evansiBaker & Pritchard,possibly native to South America, is a spider mite pest of solanaceous crops. This mite isconsidered an invasive species in Africa and Europe. A CLIMEX model was developed topredict its global distribution. The model results fitted the known records ofT. evansiexcept for some records in dry locations. Dryness as well as excess moisture stresses playimportant roles in limiting the spread of the mite in the tropics. In North America andEurasia its potential distribution appears to be essentially limited by cold stress. Detailed